Clube de ciências e unidade de aprendizagem sobre educação ambiental : contribuições para um pensar ecológico - Lippert, Beatriz Garcia (2018)
Currently, the Brazilian legislation regulates the need to discuss Environmental Education in schools. However, many practices in formal and non-formal education are still outdated and often superficial. In this context, the Science Club is a non-formal teaching and learning environment that allows the development of contents related to environmental issues. Environmental Education will be approached in the present investigation through Deep Ecology and Ecological Thinking. In this scenario, the main objective of the study is to understand the contributions of the development of a Learning Unit of Environmental Education in a Science Club for the improvement of students' Ecological Thinking. The present research used the Learning Unit as a mode of organization and curricular construction based on the "Educate by research" method. The research is qualitative and will use a case study. The research subjects are eleven students of the 6th grade of Elementary School of a private school participating in a Science Club of PUCRS (Porto Alegre / RS). The data collection instruments used were Questionnaires, Observation, Material produced by the students, Audio Recording and Field Diary. The method of data analysis used was Textual Discursive Analysis proposed by Moraes and Galiazzi (2011). As a result of the analysis, three major categories emerged: Anthropocentric perceptions of students, Intermediate steps in the Walk, and Ecocentric perceptions of students. As a result, it was possible to notice in part of the students, usually in the first encounters, anthropocentric perceptions and actions, where the role of the human being prevailed over the other forms of life. Throughout the meetings, it was possible to observe the establishment of new relations by the students from experiments, debates and questionings from monitors and classmates. In addition, it was possible to identify ecocentric tendencies in the speeches, actions and materials produced by the participants, especially in the last classes. At the end of the research it was possible to observe the improvement of students' Ecological Thinking, expressed through ecocentric perceptions, integrative thinking, complex vision, sustainable actions, critical vision and autonomy.